Legal Consequences of Establishing the Civil Rights of Illegitimate Children from the Progressive Fiqh Perspective - Fajarwati, Hiba; Nur, Iffatin; Hidayat, Fatkul (Universitas Islam Negeri Madura, 2024)
This study was motivated by a phenomenon that contrasts with justice for children, especially adulterous or born-out-of-wedlock children who cannot receive their basic rights, which should become both parents' responsibilities to fulfill. The responsibilities include the right to get recognition as children, to have their daily life needs fulfilled, to be protected, and to be legally borne. In addition, there is a phenomenon that the children do not get guardianship and inheritance rights. This problem needs to be revealed through a study using a qualitative method with a multi-site model. The research location is at the cities’ religious courts of Mojokerto, Malang, and Surabaya. Through a comprehensive study, it was found that 1) juridical implications of determining the civil rights of born-out-of-wedlock children at the Religious Courts of Mojokerto, Malang, and Surabaya showed that they have not been able to accommodate the principle of justice and the best interests of the child and have not fully implemented the principle of legal progress and 2) from the progressive fiqh (Islamic jurisprudence) perspective, legislative decisions, and juridical implications of determining born-out-of-wedlock children at the related Courts require renewal to formulate a proof mechanism of istilḥāq (children origin determination) and strengthen the Courts to carry out istilḥāq based on justice.